KETENTUAN PIDANA PEREDARAN MINUMAN BERALKOHOL OPLOSAN - Ni Ketut Sri Ratmini (VYAVAHARA DUTA, 2023)
The circulation of adulterated alcoholic beverages is a troubling problem for the police and the public. The impact of the circulation of adulterated alcoholic beverages can result in death because the drink has been mixed with substances that should not be mixed with alcoholic beverages. The mixtures that are generally used to mix alcoholic beverages are energy drinks, sweetened condensed milk, soft drinks, spirits and medicines. The mixture of these substances will produce new substances that can be harmful, even cause death. On the basis of these problems, the problem discussed in this study is about how are the rules in the provisions of criminal law regarding the circulation of adulterated alcoholic beverages circulating in the community? To answer these problems, a normative juridical research method is used. The concern for dealers of adulterated alcoholic beverages has forced the police to make efforts to prevent and stop the circulation of adulterated alcoholic beverages. In carrying out their duties, the police can take action using the provisions of Article 340 of the Criminal Code regarding premeditated murder, Article 204 of the Criminal Code concerning Unlawful Acts, the articles in Law Number 18 of 2012 concerning Food, namely in article 137 ( 1) , Article 137 paragraph (2). Article 138 and Article 146 paragraph (1) letter b. Keywords: Implosan Alcoholic Drinks, Penalties for Illegal Alcoholic Drinks Dealers, The Role of Law Enforcers